Views of pregnant women in South Western Sydney towards dental care and an oral‐health program initiated by midwives. (4th December 2013) - George, Ajesh; Johnson, Maree; Blinkhorn, Anthony; Ajwani, Shilpi; Ellis, Sharon; Bhole, Sameer
Abstract : Issues addressed: Oral health during pregnancy is important, yet is often neglected by women. A program is currently being developed for midwives in Australia to promote maternal oral health. The aim of this study was to record the views of pregnant women in Australia towards dental care and midwives promoting oral health. Methods: Using convenience sampling, a cross‐sectional survey was undertaken of 241 pregnant women attending a metropolitan hospital in South Western Sydney in 2010. Results: Only 10% of women received oral‐health promotional material during pregnancy. More than 50% reported dental problems, yet only 17% had discussed this with their midwives and less than half (44.6%) had sought dental treatment. The main barriers to obtaining dental care were: lack of awareness, safety concerns about dental treatment and dental costs. Pregnant women were more likely (P < 0.05) to see a dentist if they had received information about oral health (odds ratio (OR) 3.25, 95% CI 1.34–7.90) and had private health insurance (OR 2.47, 95% CI 1.26–4.85). Most women (> 90%) were receptive to midwives providing oral‐health education, assessments and referrals to affordable dental services. Conclusion: This study has shown that pregnant women are receiving limited dental advice and are concerned about dental costs. It has also confirmed for the first time in Australia that women are very positive about receiving oral‐health advice from midwives during their pregnancy. So what?: Oral‐health promotion programs during pregnancy should consider using midwives to increase dental awareness among women and provide pathways to affordable dental services. Abstract : This study describes the views of pregnant women in Australia towards dental care and midwives promoting oral health. The survey results showed that few women were consulting dentists despite a high prevalence of dental problems, with the main barriers being lack of dental awareness, safety concerns and dental costs. Most women were receptive to midwives promoting oral health and referring them to affordable dental services. Future strategies to improve maternal oral health should explore using midwives to increase dental awareness and providing affordable dental referral pathways.